THE INFLUENCE OF PROFESSIONAL COMPETENCE, DISCIPLINE, AND WORK TOWARDS THE CLIMATE PERFORMANCE OF THE POLICE IN HANDLING CRIMINAL CASES IN POLDA GORONTALO - Satriyo, Budi (Journal of Humanity, 2017)
Police performance is influenced various factors, including the professional competence of the Police, Work Discipline and Climate Work, besides also many other factors outside varabel above. The issue rumumsan this study include: 1. Is there a direct influence on the performance of the police professional competence in handling criminal cases at Polda Gorontalo, 2. Is there a direct influence on the performance of police work discipline in handling criminal cases at Polda Gorontalo. 3. Is there a direct influence on the performance of police work climate in handling criminal cases at Polda Gorontalo. 4. Is there a direct influence on the climate of professional competence in handling police work criminal cases in Gorontalo Police. 5. Is there a direct influence on the professional competence in handling labor discipline police criminal cases in Gorontalo Police, and 6. Is there a direct influence on the climate of labor discipline police work in handling criminal cases at Polda Gorontalo.This study conducted in Gorontalo Police with jumpal sample as many as 97 members of the Police Polda Gorontalo, this study uses Path Analysis, while the results of this study include: 1. There is a direct influence on the performance of the police professional competence in handling criminal cases at Polda Gorontalo, 2. There is a direct influence on the performance of police work discipline in handling criminal cases at Polda Gorontalo, 3. There is a direct influence on the performance of police work climate in handling criminal cases at Polda Gorontalo, 4. There is a direct influence on the climate of professional competence in handling the police work in the criminal case Police Gorontalo, professional competence 5.Terdapat direct influence on the discipline of police work in handling criminal cases at Polda Gorontalo, 5. There is a direct influence on the climate of labor discipline police work in handling criminal cases at Polda Gorontalo.